Chronic Kidney Disease of Unknown Etiology and the Island of Widows - Partridge, Arun; Chong, Louise (The Meducator, 2014)
We recently had the opportunity to spend 3 months working with La Isla Foundation (LIF), a non-governmental organization that aims to raise awareness and combat the Chronic Kidney Disease of Unknown Etiology Epidemic (CKDu) ravaging regions of Nicaragua. This epidemic has not received the international coverage and awareness that it deserves, but recent research studies and news articles have been published which have drawn global attention. There have been multiple anecdotal reports of a high chronic kidney disease prevalence in rural parts of Nicaragua and El Salvador. We assisted La Isla Foundation in their work, contributing to a variety of community development, public health, and human rights projects which gave us exposure to the important cause for which they fight.